1295. Advancing the PrEP Continuum: A Novel Collaboration Between a Public Health Department and a Federally Qualified Healthcare Center in the Southern United States. (26th November 2018) - Clement, Meredith; Eagle, Cedar; Taylor, Destry; Goldstein, Benjamin; Johnston, Barbara; Sena, Arlene
Abstract: Background: While pre-exposure prophylaxis (PrEP) is a promising strategy for HIV prevention, some high-risk persons have limited access to care, particularly Black and Latino men who have sex with men (MSM). Disparities also exist by region: the Southern United States accounts for over half of new HIV diagnoses but only a third of PrEP prescriptions. We evaluated a novel PrEP program based on a collaboration between a local department of public health (DPH) and a federally qualified health center (FQHC) providing care to underserved racial/ethnic minorities in Durham, North Carolina. Methods: In May 2015, the Durham County DPH and Lincoln Community Health Center, an FQHC, developed a program to offer PrEP services using existing resources. The model included initial no-cost screening for sexually transmitted infections (STIs), hepatitis B/C, and HIV at the DPH STI clinic, followed by referral to the FQHC for PrEP services. We profiled the PrEP continuum for patients starting at program initiation until March 2018. For PrEP initiators and non-initiators, comparisons were made using Wilcoxon rank-sum test for continuous variables, and Chi-square or FisherÕs exact tests as indicated for categorical variables. Results: Of 196 unique patients evaluated in the STI clinic and referred to the FQHC, 117 (60%) persons attended their initial PrEP appointments. Among these, 84 (43%) filled a PrEP prescription, 69 (35%) persisted in care for at least three months, and 58 (30%) reported >90% adherence at follow-up (see figure). Among those presenting for initial appointments ( n = 117), more than half were Black ( n = 62, 53%) and 21 (18%) were Latino. Most were MSM ( n = 95, 81%) and 9 were transgender. Almost half ( n = 55, 47%) were uninsured. We found statistically significant differences between PrEP initiators vs. noninitiators based on race/ethnicity ( P = 0.02), insurance status ( P = 0.05), and history of sex work ( P = 0.05). Conclusion: A collaborative model of PrEP care between a DPH and an FQHC in the Southern United States was able to reach predominantly Black and Latino MSM at high-risk for HIV. Although this program is sustainable, efforts to improve steps along the PrEP care continuum are still needed in this population. Disclosures: A. Sena, Gilead: Grant Investigator, Research grant.